Tourisme, écotourisme et stratégies de développement dans la Caraïbe - Olivier Dehoorne; Pascal Saffache; Dominique Augier (Études Caribéennes)
Tourism has become the driving force of the island economies of the Caribbean basin since the latter part of the 1980s. Within this island realm, the traditional plantation economies have gone through an economic crisis while tourism. On the other hand, has taken on considerable importance (19.2 billion dollars and a 7% annual growth rate since 1990. Nevertheless this growth has not been without its economic problems (a low level of local linkages) and environmental (concentration of tourist flows). Caribbean island tourism is now concentrating its efforts on developing new strategies based on ecotourism perspectives. Tourism, ecotourism and development strategies in the Caribbean.